El método heurístico en el aprendizaje de funciones lineales y potencia en los estudiantes del décimo año de educación general básica - Benavidez Loaiza, Jonathan Israel (2023)
This research aims to determine the importance of the heuristic method in the learning of linear functions and power in students in the tenth year of primary general education. For this purpose, the search for information was carried out considering the variables of the study, in addition, in the methodology, it was specified that this work is framed in a documentary design with a qualitative approach and descriptive scope; in order to fulfill planted objectives, the file and the documentary analysis were used as a technique, on the other hand, for the collection of information, instruments such as the mixed content cards and the search log were used. According to the results obtained, the importance of the heuristic method in the learning of linear functions and power is ratified since it provides a series of strategies and techniques. Finally, a methodological guide for learning linear functions and management through the implementation of the heuristic method is proposed. Keywords: teaching – learning, heuristic method, heuristic technique, and strategies.